2009
DOI: 10.1016/j.juro.2009.04.078
|View full text |Cite
|
Sign up to set email alerts
|

German Version of the Pediatric Incontinence Questionnaire for Urinary Incontinence Health Related Quality of Life

Abstract: The German version of the Pediatric Incontinence Questionnaire is a valid and reliable outcome measure to assess health related quality of life in children and adolescents with urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Patients' HRQOL, as measured with the PEMQOL‐SF child impact scale, did not show significant associations with age, gender, diagnostic subgroup, symptom severity, comorbid constipation or fecal incontinence. This result is in contrast to recent studies on HRQOL in children with urinary incontinence, which showed impaired HRQOL in older children, children with comorbid bowel problems, children with increased frequency of daytime incontinence episodes and children with combined daytime/nighttime incontinence 19,20. The above‐mentioned findings also do not match the findings of Petersen et al,29 who found a significant association between increased symptom severity and reduced patients' HRQOL.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Patients' HRQOL, as measured with the PEMQOL‐SF child impact scale, did not show significant associations with age, gender, diagnostic subgroup, symptom severity, comorbid constipation or fecal incontinence. This result is in contrast to recent studies on HRQOL in children with urinary incontinence, which showed impaired HRQOL in older children, children with comorbid bowel problems, children with increased frequency of daytime incontinence episodes and children with combined daytime/nighttime incontinence 19,20. The above‐mentioned findings also do not match the findings of Petersen et al,29 who found a significant association between increased symptom severity and reduced patients' HRQOL.…”
Section: Discussioncontrasting
confidence: 92%
“…Concerning the psychometric properties of the PinQ, BOWER et al reported a two‐factored structure with a 5‐item intrinsic scale (Cronbach's alpha α = 0.91) and the 16‐item extrinsic scale (Cronbach's alpha α = 0.72) 15. This structure could not be replicated in a study of BACHMANN et al who found a factorial model with only one scale 19…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is in contrast to recent studies on HRQOL in children with urinary incontinence, which showed impaired HRQOL in older children, children with comorbid bowel problems, children with increased frequency of daytime incontinence episodes and children with combined daytime/nighttime incontinence. 19,20 The above-mentioned findings also do not match the findings of Petersen et al, 29 who found a significant association between increased symptom severity and reduced patients' HRQOL. Additionally, the lack of association between HRQOL and clinical symptoms highly challenges the validity of the PEMQOL-SF for clinical use, as it is desirable that HRQOL instruments used in clinical practice reflect different clinical situations through dissimilar HRQOL scores, as, for example, in the study of Natale et al, 14 who found differing levels of HRQOL between children with overactive bladder and voiding postponement.…”
Section: Discussionmentioning
confidence: 67%
“…15 This structure could not be replicated in a study of BACHMANN et al who found a factorial model with only one scale. 19 DISABKIDS DCGM-10/-12 Questionnaire…”
Section: Pediatic Incontinence Questionnairementioning
confidence: 99%